Thinking Outside of The Box! It Is High Time - Riddance of Archaic Methodology - The Honorable M. Nawaz Wahla (NUST Journal of Social Sciences and Humanities)
The overarching objective of this opinion piece is endlessly learning and adjusting to the challenges of the modern academic world. These observations and reflections are based on first-hand experience teaching three courses: civil procedure, the law of evidence, and legal drafting. Throughout the semester, there was extensive interaction with the students - thrice a week for approximately 3 hours each class. This opinion underscores the importance of thinking outside the box and strictly adhering to the rules, regulations, and university policies in its letter and spirit across the board, whether it pertains to student attendance, assignments, projects, or grading. Also, the opinion touches on the demerits of archaic teaching and offers few recommendations for fixing it. The semester has flown away in a blink of an eye. It seems like yesterday flying from New York to Islamabad. My enthusiasm peaked and was entirely driven by the desire to give back to my birth country by teaching law as taught in the United States of America – specifically, to those who would never have a chance to go abroad for studies. The underlying desire had been and will always be - to share my approximately forty (40) years of experience, knowledge, and daily breathing in the life of law in the world's litigious society – the United States of America. In April 2023, Dr. Asif Khan, NUST head of the law department, came to Washington, DC. We both were judging the JESSUP Competition. We discussed the idea of my teaching Civil Procedures, Evidence, and Legal Drafting for the fall semester of 2023. Despite fierce opposition from family and close friends, I agreed to the proposal. I started preparing the coursework/syllabus and everything needed for the semester.